2020
DOI: 10.3991/ijim.v14i06.12035
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Indonesian Pre-Service Teachers’ Use of m-LMS: A Mix Method Study

Abstract: The purpose of this research is to investigate factors affecting Indonesian pre-service teachers’ (PSTs) teachers’ use of m-learning management systems (m-LMS) in higher education. The difference regarding the use of m-LMS based on some demographic information namely gender, university, year in university, and age are also reported as well as gaining an in-depth understanding of the use of m-LMS in Indonesian universities. To achieve this, two approaches, quantitative and qualitative, were applied. First, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 15 publications
5
14
0
1
Order By: Relevance
“…This study was conducted with 130 university students in Sweden. Another article [45] investigated Indonesian instructors' use of m-LMSs from the teachers' perspective. Here the researchers used similar variables as in TAM and concluded that the use of m-LMS systems is related to teachers' perceived usefulness and perceived ease of use, subjective norms and attitudes of self-efficacy, and supporting conditions.…”
Section: Recent Research and M-lmsmentioning
confidence: 99%
“…This study was conducted with 130 university students in Sweden. Another article [45] investigated Indonesian instructors' use of m-LMSs from the teachers' perspective. Here the researchers used similar variables as in TAM and concluded that the use of m-LMS systems is related to teachers' perceived usefulness and perceived ease of use, subjective norms and attitudes of self-efficacy, and supporting conditions.…”
Section: Recent Research and M-lmsmentioning
confidence: 99%
“…TAM proposed that EE is a critical factor for the usage of a technology. Previous studies that deployed TAM found that the EE is essential variable for the use of technology such as ML [23]- [26], [29]. In this study, EE is expected to have a positive effect on the BI to use ML.…”
Section: Effort Expectacny and Bimentioning
confidence: 77%
“…In the context of ML, the PE of ML in accessing high quality content of learning material is important for the students to use the technology [18], [22]. Prior literature found that the PE has a significant effect on the BI to use ML [23]- [26]. In this study, it is proposed that PE will have a positive effect on BI to use ML by Iraqi undergraduate English literature students.…”
Section: Performance Expectancy and Bimentioning
confidence: 89%
“…Online multimedia was developed using a web Learning Management System (LMS) system. The use of LMS makes operational management to be easier than that of other media (Aman, Prasojo, Sofwan, Mukminin, Habibi, & Yaqin, 2020). The process of designing, operating, and editing that was easy and fast allows developers to develop learning resources properly.…”
Section: Resultsmentioning
confidence: 99%